On the Implication of Pictured Fortification in Roman Art - Medennikova, Alexandra E.; Karelin, Dmitry A. (Actual Problems of Theory and History of Art, 2021)
There are many examples of depictions of city walls, fortresses, and military camps in Roman art. The goals of the study are to classify the examined depictions, to reveal the peculiarities and architectural details of fortifications, which are little-known according to archaeological data, and to analyze the features of the studied depictions. They can be divided into several types: images on coins, medals, and in codices; frescoes or mosaics; objects of applied art and architectural models; sculptural reliefs.The studied images show many architectural peculiarities of Roman military architecture unknown to archaeology and have common features. For example, the masonry is usually shown in the same manner: it is monumental and made of huge rectangular blocks.The article singles out three main meanings of the examined images: the architectural landscape, the idea of a city (urbs) and the depiction of sacral borders (the pomerium and others).
Keywords: wall paintings; fresco; mosaic; coins; models; wall; tower; fortress; military camp; gate; Roman art; architectural backgrounds